Elevation based, fuel consumption predictions using a gami cation model : the South African Truck Simulator - Swanepoel, Anieke (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2018.